PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Pada Rumah Makan Suka Ramai Kota Kupang) - Mamida J.Toleu; Anthonius B. Messakh; Juita L.D. Bessie (Universitas Nusa Cendana, 2017)
This research was conducted at Suka Ramai Restaurant, Kupang City.The purpose of this researchis to know the influence of Service Quality consisting of Tangible, Responsiveness, Reliability,Assurance, and Empathy partially and simultaneously to Customer Satisfaction. The population inthis reseach were Suka Ramai Restaurant’s customers. Samples taken as many as 100 respondentsby using Accidental Sampling Technique. The analysing tool in this research is Multiple LinearRegression Analysis. The analysis includes: Multiple Analysis Test, Classical Assumption Test,Hypothesis Testing (F Test And t Test) And Coefficient of Determination Analysis (R2). The resultof research had obtained Regression Equation : Y= 4,737 + 0,524X1 + 0,461X2 + 0,145X3 +0,257X4 + 0,420X5. Based on statistical data analysis of Classical Assumption Testing, RegressionModel is normally distributed. The result of Hypothesis Testing using t Test is obtained that the 5independent variables have significant effect partially on Customer Satisfaction variable. While theresult of F Test shows that the 5 independent variables have a significant effect simultaneously onCustomer Satisfaction. The value of Adjusted R Square of 0,829 indicates that 82,9% of CustomerSatisfaction variable is influenced by independent variable in the Regression Equation. While therest 17,1% of Customer Satisfaction variable is influenced by other variables that are not discussedin this research.Keywords : Service Quality (Tangible, Responsiveness, Reliability, Assurance, And Empathy)And Customer Satisfaction.